IgA2 immune complexes selectively promote inflammation by human CD103+ dendritic cells - Mes, Lynn; Steffen, Ulrike; Chen, Hung-Jen; Veth, Jennifer; Hoepel, Willianne; Griffith, Guillermo Romeo; Schett, Georg; den Dunnen, Jeroen (Frontiers in Immunology, 2023)
While immunoglobulin A (IgA) is well known for its neutralizing and anti-inflammatory function, it is becoming increasingly clear that IgA can also induce human inflammatory responses by various different immune cells. Yet, little is known about the relative role of induction of inflammation by the two IgA subclasses i.e. IgA1, most prominent subclass in circulation, and IgA2, most prominent subclass in the lower intestine. Here, we set out to study the inflammatory function of IgA subclasses on different human myeloid immune cell subsets, including monocytes, and in vitro differentiated macrophages and intestinal CD103+ dendritic cells (DCs). While individual stimulation with IgA immune complexes only induced limited inflammatory responses by human immune cells, both IgA subclasses strongly amplified pro-inflammatory cytokine production upon co-stimulation with Toll-like receptor (TLR) ligands such as Pam3CSK4, PGN, and LPS. Strikingly, while IgA1 induced slightly higher or similar levels of pro-inflammatory cytokines by monocytes and macrophages, respectively, IgA2 induced substantially more inflammation than IgA1 by CD103+ DCs. In addition to pro-inflammatory cytokine proteins, IgA2 also induced higher mRNA expression levels, indicating that amplification of pro-inflammatory cytokine production is at least partially regulated at the level of gene transcription. Interestingly, cytokine amplification by IgA1 was almost completely dependent on Fc alpha receptor I (FcαRI), whilst blocking this receptor only partially reduced cytokine induction by IgA2. In addition, IgA2-induced amplification of pro-inflammatory cytokines was less dependent on signaling through the kinases Syk, PI3K, and TBK1/IKKε. Combined, these findings indicate that IgA2 immune complexes, which are most abundantly expressed in the lower intestine, particularly promote inflammation by human CD103+ intestinal DCs. This may serve an important physiological function upon infection, by enabling inflammatory responses by this otherwise tolerogenic DC subset. Since various inflammatory disorders are characterized by disturbances in IgA subclass balance, this may also play a role in the induction or exacerbation of chronic intestinal inflammation.